Associations among fear of childbirth, resilience and psychological distress in pregnant women: A response surface analysis and moderated mediation model - Mei, Xiaoxiao; Mei, Ranran; Liu, Yuling; Wang, Xinqin; Chen, Qianwen; Lei, Youjin; Ye, Zengjie (Frontiers in Psychiatry, 2022)
This study was designed to estimate the associations among fear of childbirth, resilience and psychological distress. A total of 1,060 Chinese pregnant women derived from Be Resilient to Postpartum Depression (BRPD) were recruited from two hospitals between January and April 2022. A dominance analysis was performed to determine the relative importance of different predictors followed by a response surface analysis and a moderated meditation analysis.In terms of psychological distress, resilience and fear of childbirth could explain 41.6% (0.148/0.356) and 33.1% (0.118/0.356), respectively. Pregnant women with high resilience-low fear of childbirth had significantly lower levels of psychological distress than those with low resilience-high fear of childbirth. The mediating role of resilience and the moderating effect of adverse childhood experiences were also identified. Therefore, resilience, fear of childbirth and adverse childhood experiences may be three important factors to psychological distress in Chinese pregnant women.